Adesão ao Programa Nacional de Alimentação Escolar: fatores associados e a qualidade nutricional das refeições - Benvindo, Joyce Larissa da Silva [UNIFESP] (2018)
Introduction: The National School Feeding Program (PNAE) is considered one of the largest social policies in Brazil, through the provision of meals to all students in basic education, enrolled in the public school system. In spite of such relevance, few studies explore the topics that involve PNAE, being a field of interest the students' adherence to the program, as well as the quality of the menus. Objective: To evaluate the adherence of the studies to the PNAE and its intervening factors, as well as to analyze the nutritional quality of the menus. Material and Methods: A cross-sectional study carried out in 16 municipalities in the State of São Paulo, with elementary school students II (6 th to 9 th) in a partial period. A semi-structured and self-administered questionnaire was used with 25 questions and the weekly menus were collected from the nutritionists at each site. It was considered adherence to PNAE consumption of three or more days in the school feeding week. The menus offered one or two meals a day for the students, being subdivided into "Menu I", defined as the main meal during the period of study; and "Menu II", as the second meal, food served to the students as a complement. For the qualitative analysis of the menus, the Food Guide for the Brazilian Population and the Quality Indicator of the School Meals Menu (IQCAE) were used as reference. A descriptive analysis of the data was performed, and the chi-square test, Regression model and Student's t test were used for inferential analysis to associate variables of interest with students' adherence to the program. Results: The study population consisted mostly of students between 11 and 14 years old (90%), boys (52%), enrolled in 17 schools. There was high acceptance (85.1%) and low adherence to PNAE (47.5%). The presence of canteens and external food sellers and the habit of buying food in these trades; take home snacks; the period of study (evening); and noisy spaces for consumption of PNAE meals decreased adherence to the program. Of the 16 menus analyzed, half provided two meals and only one was not prepared by a nutritionist. The Menu I mainly offered lunch, showed good nutritional quality (3.29 points) and often offered vegetables and foods in natura or minimally processed in most of the municipalities. Menu II only had snacks, low quality (1.11 points) and daily supply of processed and ultraprocessed items. It was observed the presence of prohibited items in the menus and low supply of fruits, with 48.6% of the municipalities providing none or only 1 portion of fruit in the week. There was no association between the nutritional quality of the menus and adherence of the students to the program (p> 0.01). On the other hand, meals considered "bad" and "repetitive" by schoolchildren were associated with non-adherence, and high acceptance showed a positive association with adherence. Conclusion: Students' adherence to PNAE is negatively influenced by the presence of canteens and external food sellers, and by the distribution conditions and the space for eating meals. Although the quality of the menu does not affect the adherence to the PNAE, it’s necessary to increase the supply of fruits in the menus and mainly to improve the quality of the Menu II, which had a high supply of ultraprocessed products.